The use of management accounting in the formation of an ESG strategy in the agro-industrial complex (Journal of Economic Research & Business Administration, 2025)
ESG principles have become a model for sustainable business development, helping organizations solve environmental, social, and management challenges. The principles of ESG (Environmental, Social, Governance) have a guiding and authoritative influence in various business areas. In this regard, the large number and complexity of business processes in the agro-industrial complex require the formation of an ESG strategy. This, in turn, is carried out through a quality management accounting system.The main purpose of this article is to substantiate the role and importance of management accounting in the formation of an ESG strategy in the agro-industrial complex using the example of a specific organization. Management accounting as an object of research provides the collection, systematization, analysis and interpretation of data necessary for the implementation of the ESG strategy, and ESG imposes new requirements on the content, methods and tools of management accounting.In the course of the research, theoretical and methodological methods, methods of modeling and visualizing relationships were used. A systematic approach allows us to consider Management Accounting and ESG strategy as interrelated elements of a common corporate governance system. Content analysis is used to study international and national reporting standards, corporate ESG reports, and companies' internal rules. Comparative analysis revealed the advantages of managerial accounting over financial accounting. Using the ESG strategic map, it was shown which elements of the accounting system ensure the achievement of the Sustainable Development Goals. In order to review the reporting form based on non-financial information compiled by the organization in accordance with ESG principles, the data of Aitasаgro holding was analyzed.The theoretical significance of the article lies in the theoretical substantiation of the relationship between management accounting and the ESG concept and the systematization of ESG indicators as objects of management accounting.The practical significance of the article is considered valuable due to its description of the compatibility of ESG reporting and management accounting.In conclusion, the study provides a comparative description of the advantages of management accounting in comparison with the financial report in the implementation of ESG principles.  Linking ESG indicators with the management accounting system makes it possible to form a unified information base for the analysis of financial and non-financial information.Key words: ESG strategy, Management accounting, agro-industrial complex, sustainable development.